Study On Streamlined Process Improvement By Using Value Stream Mapping In Automotive Seating Company: A Case Study - A. P., Puvanasvaran; T.S.N., Stephanie; N., Norazlin (Penerbit UTeM, 2013)
Streamlined process improvement is often one of the tools applied during the performance improvement plan at which it is an effective way of bringing about positives improvement to the processes. Value Stream Mapping is a qualitative tool by which described the process in detail about how it operates in order to create flow. Through the value stream is regarded as an important tool in the implementation of lean manufacturing at where it identifies the waste in system which paving the way for a successful lean implementation. The paper discussed the findings from the development of the Current State Value Stream Mapping (CSVSM) and the reduction in non value added time that can be obtained after the development of Future State Value Stream Mapping (FSVSM). The result of this paper indicates that development of the Value Stream Mapping from CSVSM to FSVSM has led to reduction in non-value added time from 11.76 days to 3.00 days. The suggestions of potential improvements opportunities are proposed for the Future State Value Stream Mapping after analyzing the problem statements.